Defending the Accused: The Impact of Legal Representation on Criminal Trial Outcomes in Victoria, Australia 1861–1961. Issue 1 (2nd January 2017) - Piper, Alana; Finnane, Mark
ABSTRACT: Access to legal representation by accused felons was entrenched as part of the adversarial system from the early nineteenth century, but a substantial minority of defendants remained undefended at superior court level well into the twentieth century. Using a sample of criminal trials collected across a crucial hundred-year period that saw the development of incipient legal assistance schemes, this article seeks to examine what effect the presence of defence counsel had on individual trial results. It is shown that there was a significant association between defence status and a variety of outcomes, including pleas, verdicts, trial length, bail status and sentencing. This relationship was to some extent affected by the specific offence with which the accused was charged, but remains evident across various other factors, including defendant ethnicity, sex, occupation and age, and lawyer assigned to the case. The results suggest that representation was highly desirable for defendants throughout this period.